Dosing Nomograms for Attaining Optimum Concentrations of Meropenem by Continuous Infusion in Critically Ill Patients with Severe Gram-Negative Infections: a Pharmacokinetics/Pharmacodynamics-Based Approach - Pea, Federico (American Society for Microbiology, 2012)
The worrisome increase in Gram-negative bacteria with borderline susceptibility to carbapenems and of carbapenemase-producing Enterobacteriaceae has significantly undermined their efficacy. Continuous infusion may be the best way to maximize the time-dependent activity of meropenem. The aim of this study was to create dosing nomograms in relation to different creatinine clearance (CL(Cr)) estimates for use in daily clinical practice to target the steady-state concentrations (C(ss)s) of meropenem during continuous infusion at 8 to 16 mg/liter (after the administration of an initial loading dose of 1 to 2 g over 30 min). The correlation between meropenem clearance (CL(m)) and CL(Cr) was retrospectively assessed in a cohort of critically ill patients (group 1, n = 67) to create a formula for dosage calculation to target C(ss). The performance of this formula was validated in a similar cohort (group 2, n = 56) by comparison of the observed and the predicted C(ss)s. A significant relationship between CL(m) and CL(Cr) was observed in group 1 (r = 0.72, P < 0.001). The application of the formula to meropenem dosing in group 2, infusion rate (g/24 h) = [0.078 × CL(Cr) (ml/min) + 2.85] × target C(ss) × (24/1,000), led to a significant correlation between the observed and the predicted C(ss)s (r = 0.92, P < 0.001). Dosing nomograms based on CL(Cr) were created to target the meropenem C(ss) at 8, 12, and 16 mg/liter in critically ill patients. These nomograms could be helpful in improving the treatment of severe Gram-negative infections with meropenem, especially in the presence of borderline susceptible pathogens or even of carbapenemase producers and/or of pathophysiological conditions which may enhance meropenem clearance.